MATERNAL KNOWLEDGE REGARDING THE FIRST 1000 DAYS OF LIFE WITH THE INCIDENCE OF STUNTED CHILDREN UNDER THE AGE OF FIVE IN THE WORKING AREA OF SUKOMULYO COMMUNITY HEALTH CENTER - Kevin Alexander Danuseputro; Isabel Nauli Anggia Pangaribuan; Ricky Stefanus Tanuy; Adisti Kristianingrum; Grace Alverina; Andri Danika; Felicia Margaret; Stefanny Ckaudia Centis Da Lopez; Farah Vizah; Leonardo Adi Wibowo; Komang Yoga Suryawan; Zanuba Qottrun Nada; Lukas Slamet Rihadi; Florentina Sustini; Dewa Ayu Liona Dewi; Yudhiakuaru Sincihu; Steven Wijono; Titik Ernawati (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Stunting is a global and national health problem. The World Health Organization (WHO) determines that if the prevalence of stunting is between 30-39%. Based on the reports of Riskesdas in 2010, it was reported that 35.6% of Indonesian children under five were stunted. Stunting is a condition that describes a linear growth disorder characterized by height that is below normal standards for age and sex that is commonly associated with malnutrition and chronic (non-endocrine) infections. The stunting intervention was focused on 1000 Hari Pertama Kehidupan (HPK) period, which is a golden period of a child and if not utilized appropriately, permanent damage could occur. Objective: To determine the correlation between maternal knowledge levels regarding 1000 HPK and the incidence of stunting in children under five. Methods: This study used an observational analytic method with a cross sectional design. Sampling was done with consecutive sampling technique. In this study, will be examined for body length using a stadiometer. After that, the mother will be interviewed to find out the correlation between mother's knowledge regarding 1000 HPK and the incidence of stunting in toddlers. Then the stunting and normal children will be grouped based on the standardized WHO growth chart. Results: Kendall's tau-b statistical test showed a significant relationship (p = 0.000) with positive moderate strength correlation (τ = 0.442). Conclusion: There is a significant relationship and a moderate strength positive correlation between the mother's level of knowledge regarding 1000 HPK and the incidence of stunting Keywords: Maternal knowledge of 1000 HPK, Stunted, Children under five